Career Development in the Indonesian National Police (Analysing the Effect of Motivation, Competence and Self-Efficacy on Career Commitment and Its Implications) - Andreas Ricky Trianto; Lina Miftahul Jannah; Eko Prasojo (Al-Makki Publisher, 2026)
Career development in the Indonesian National Police (Polri) institution is a strategic issue as the complexity of tasks, organizational dynamics, and the demands of professionalism and public trust increase. The National Police's career development system emphasizes the principles of transparency, objectivity, and professionalism, but still faces challenges in competency-based and achievement-based implementation. This study aims to analyze the influence of motivation, competence, and self-efficacy on career commitment and its implications for the career development of members of the National Police. This study uses a quantitative approach with empirical analysis based on career development and motivation theory, including expectancy theory, self-efficacy theory, and the concept of career commitment. Data were analyzed to test the relationship between variables and formulate relevant career development models in the context of the National Police organization. The results of the study show that intrinsic and extrinsic motivation have a significant effect on career commitment. Competencies, especially continuous learning and innovation skills, improve self-efficacy and career development readiness. Self-efficacy has been shown to strengthen career commitment, which further has a positive impact on career development. However, there are still gaps in the aspects of interpersonal competence and career resilience that require more optimal organizational support. Effective career development of the National Police requires synergy between competency-based organizational policies and individual initiatives in sustainable planning and self-development. A collaborative and achievement-oriented career development model is key to improving the professionalism and sustainability of the institution.